Risk Management Analysis Based on Environmental and Social Aspects Case: PT A - Permata Kardina Putra; Ancella Anitawati Hermawan (Budapest International Research and Critics University, 2021)
This study aims to analyze environmental and social risk management in fertilizer companies. Environmental and social aspects are essential for fertilizer companies because chemicals as the primary raw material risk pollution to the environment. In addition to the environmental impact, the Company also has a potential impact from business activities on employees and the surrounding community. Companies need to implement risk management related to environmental and social aspects in an orderly manner. This study uses qualitative methods using interviews and documentation. The study results indicate that the Company has made efforts to carry out risk management related to social and environmental aspects. However, companies in implementing environmental performance are carried out partially so that the measurement of sustainability strategies does not include environmental and social factors as key performance indicators. The absence of key performance indicators for environmental and social aspects impacts the Company's ineffectiveness in managing environmental and social risks. Companies need to make key performance indicators based on social and environmental elements to achieve sustainability goals.